Indigenous Intermediaries: New perspectives on exploration archives - Konishi, Shino; Nugent, Maria; Shellam, Tiffany (ANU Press, 2015)
This edited collection understands exploration as a collective effort and experience involving a variety of people in diverse kinds of relationships. It engages with the recent resurgence of interest in the history of exploration by focusing on the various indigenous intermediaries - Jacky Jacky, Bungaree, Moowattin, Tupaia, Mai, Cheealthluc and lesser-known individuals - who were the guides, translators, and hosts that assisted and facilitated European travellers in exploring different parts of the world. These intermediaries are rarely the authors of exploration narratives, or the main focus within exploration archives. Nonetheless the archives of exploration contain imprints of their presence, experience and contributions. The chapters present a range of ways of reading archives to bring them to the fore. The contributors ask new questions of existing materials, suggest new interpretive approaches, and present innovative ways to enhance sources so as to generate new stories.